KETIDAKSAMAAN PADA FUNGSI Q-GAMMA - ., Baiduri (Jurnal Gamma, 2009)
Alsina and Tomas (2005) discuss about inequaty of the gamma function by geometricalapproach. Sandor (2005) and Baiduri (2008) discuss about some inequalities that involves the gammafunction based on the series representaion of psi function. Based on these results and use samemethod, this paper discusses some inequalities involves the q-gamma function.